Policy Review and Development Planning Recommendations for Infiltration Wells in Indonesia - Pambudi, Andi Setyo; Bambang Pramujo (Universitas Merdeka Malang, 2025)
Managed aquifer filling has become more prevalent in recent years as an option for alleviating water scarcity and flood prevention. In this regard, infiltration wells are considered one of the technical solutions for water resource conservation efforts that are more in line with environmental issues. The dynamics of infiltration wells, from philosophy and planning to evaluation, are various parties' concerns in the context of sustainable development. The benefits, problems, and impacts of infiltration wells are engaging to study further based on multiple existing studies. This study aims to provide more comprehensive considerations for improving infiltration well development policies in the future. The analytical method used is a qualitative approach through literature studies. Several regulations are used as material for analysis, starting from the level of laws to operational decisions from local governments. The literature study also takes the essence of various journals related to essential issues in constructing infiltration wells in Indonesia from technical and non-technical aspects. The study results recommend more scrutiny in planning infiltration wells according to regional characteristics, strengthening regulations, and triple helix collaboration (government, community, business world) in implementation, maintenance, financing, and periodic monitoring and evaluation.